C-reactive protein and neutrophil–lymphocyte ratio as predictors of mortality in coronavirus disease 2019 - Ergenç,Hasan (2021)
SUMMARY OBJECTIVE: This study investigates whether C-reactive protein, platelet–lymphocyte ratio, and neutrophil–lymphocyte ratio could be useful to predict mortality in COVID-19. METHODS: Data of 635 patients with COVID-19 followed up in Sinop Ataturk State Hospital from February to May 2020 were evaluated retrospectively. Diagnosis of COVID-19 was made according to the interim guidance of the World Health Organization. Patients were grouped into two groups based on mortality as survived and non-survived patients. Age, gender, neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, and C-reactive protein of the groups were investigated and compared. RESULTS: The mean age of the participants was 55.8±22.3 years. Among the patients, 584 survived and 51 patients died. Age was significantly different between the groups, 54.2±22.3 in the survived group and 75.6±11.1 in the dead group (p=0.000). In addition, neutrophil, C-reactive protein, and neutrophil–lymphocyte ratio values were significantly higher in the dead group (p=0.000). platelet–lymphocyte ratio was slightly higher in the dead group, but this difference was not significant (p=0.42). The area under the curve values for age, lymphocyte, platelet, C-reactive protein, and neutrophil–lymphocyte ratio are 0.797, 0.424, 0.485, 0.778, and 0.729, respectively. CONCLUSIONS: Our results showed that neutrophil–lymphocyte ratio and C-reactive protein are significantly higher in patients leading to death and could be effective biomarkers in predicting COVID-19 fatality. Furthermore, C-reactive protein could be used as an independent biomarker to predict death in patients with COVID-19, regardless of gender and age (p=0.000).